Experimental study on the effects of stern bulb arrangement on the slamming load - Park, Jongyeol; Choi, Ju Hyuck; Lee, Hyun-ho; Rhee, Shin Hyung (International journal of naval architecture and ocean engineering, 2020)
The present study concerns the stern slamming load of container carriers, with stern bulb arrangement variation. First, a series of wedge drop tests were conducted using simple wedge models with fixed deadrise angles, and tests with the cross-section models of practical container carrier sterns were followed. The deadrise angle of the simple wedge ranged from 0° to 10°. The pressure measurement results of the simple wedge drop tests were distributed between empirical formula and analytic solution, so the experimental setup was validated. In the cases of practical hull cross-sections, the water entry of the bulb prior to that of the transom resulted in characteristic water film generation and delayed pressure peak appearance. The trapped air between the bulbs damped the pressure in the twin skeg hull case, reducing the pressure peak and causing the pressure oscillation during water entry.